Festivals, Heritage, and Environment: A Decadal Review (2015–2025) - Saira Iqbal,; Arslan Butt, (Dialogue Social Science Review (DSSR), 2025)
This research examines the changing cultural, ecological, and socio-political aspects of South Asian festival traditions in India and Pakistan in an interdisciplinary literature review between 2015 and 2025. Rooted in the discourses of environmental humanities, cultural anthropology, and heritage studies, the study identifies three connected thematic paths: festivals as manifestations of intangible cultural heritage, human-nature relationships in ritual practices, and dynamic adjustment of festivals in the face of socio-political instability and digital change. Using a qualitative visual mapping method like a word cloud, the research identifies salient terminologies and thematic overlaps, increasing methodological transparency. Research findings indicate festivals as living cultural systems that encode ecological knowledge, maintain communal identities, and mediate contemporary challenges like climate change, urbanization, and religious pluralism. Despite such richness, the literature exhibits some critical shortcomings, such as a shortage of comparative, cross-border work, and scant exploration of digital hybridity, as well as little focus on intergenerational transfer and climate exposures. The work suggests future research that includes ethnofuturism—a frame of reference being increasingly applied to European cultural studies—to imagine culturally embedded but future-oriented festival practices in Asian settings. This integration can be used to reimagine festivals not just as archives of heritage but as adaptive methodologies for ecological and cultural sustainability in the context of global uncertainty. Keywords: South Asian Festivals, Intangible Cultural Heritage, Environmental Humanities, Ritual Ecology, Cultural Resilience, Digital Transformation, Ethno-futurism